Application of Flexible Wearable Sensors for Revolution of Personalized Medicine in the Age of Digital Health - Yu, Wenfei (Transactions on Materials, Biotechnology and Life Sciences, 2024)
With the advent of the digital health era, flexible wearable sensors show great potential in personalized medicine and health monitoring. This research discusses recent advances in polymer-based flexible sensors that enable real-time, non-invasive monitoring of vital signs and physiological parameters, which are essential for early diagnosis and timely intervention in health conditions. Researchers are developing new flexible materials to adapt to the shape and dynamics of the human body while maintaining comfort and performance. By integrating advanced nanotechnology and environmentally friendly biomimetic materials such as MXene quantum dots (MQDs) and molybdenum disulfide (MoS2), researchers have developed sensors with high sensitivity and excellent biocompatibility. These sensors can not only provide continuous health data, but also realize remote transmission and encryption of data through wireless modules, ensuring user privacy and data security. In addition, new signal processing modules and multimodal sensors offer a wide range of application possibilities for intelligent perception, interactive devices and health motion monitoring. The research also discusses the revolutionary role of flexible wearable sensors in the future of health management, and how to process and analyze the large amounts of data generated by sensors. These studies not only promote the progress of health monitoring technology, but also provide new solutions for personalized medicine and smart medicine.